A Tool for Measuring the Smart Readiness of Existing Buildings and Cities in Egypt–Focusing on Energy Sector: Towards Smart Ready Checklist. Issue 1 (31st December 2022) - Galal, Abeer; Elariane, Sarah
ABSTRACT: The world is witnessing a shifting toward smart cities and the use of technology in cities. There are many rating systems to measure the smart readiness of existing buildings and cities, but they are not suitable in the Egyptian context. However, Egypt promotes sustainable and smart development through many codes, guidelines and rating systems. This research aims to develop a tool to measure the smart readiness of existing buildings and cities to help decision-makers determine the level of intervention needed for a building or a city to be smart. An induction research approach is used to deduce the smart readiness indicators for existing buildings and cities. The research ends by proposing 'Checklists' for measuring the smart readiness of Egyptian existing buildings and cities stock.